Έρημα λίκνα: Το τραύμα και η μοναξιά - Γαλανάκη, Ε. (Τετράδια Ψυχιατρικής, 2013)
In this paper, we examine the relation between psychic trauma in the first years of life and loneliness. We selected a representative sample of important ''natural experiments'', as revealed in the work of Anna Freud, René Spitz as well as James and Joyce Robertson. The adverse effects of child neglect, abuse, abandonment, war, separation from parents, life in inappropriate institutions, and hospitalization are presented and discussed. Our analysis shows that among children with early and multiple trauma, the quality of loneliness, the normal fear of loneliness, separation anxiety in the relations with parents, siblings and peers, ways of coping with loneliness (e.g., forming relationships, play, fantasies, defense mechanisms), the capacity to be alone and the creative use of solitude, suffer and constitute major problems of traumatized children. We suggest that trauma can be healed through binding, as a restitution of the break in the continuity resulting from trauma, as well as sharing.